ANALISIS KETIDAKLENGKAPAN PENGISIAN INFORMED CONSENT PADA PASIEN BEDAH PARU DI RSUD PASAR MINGGU - Akhmad Setiawan; Irda Sari (Bajang Institute, 2021)
Informed consent is an agreement given by the patient or the patient's family on the basis of an explanation of the medical action to be performed on the patient. Informed consent is the doctor's explanation of the actions to be taken, and a statement that the patient has understood and agreed about the information submitted by the doctor. Informed consent must be filled in completely, but still found incomplete filling on the informed consent sheet in some items. The purpose of this study is to find out the factors that cause incomplete filling of informed consent in cases of pulmonary surgery in Pasar Minggu Hospital. This research method uses qualitative descriptive methods. Results From the analysis of 145 informed consent in May and June 2021 there were 70 informed consent (42.8 %) which is still incomplete and there are 75 informed consent (51.7 %) complete. Incompleteness is more common in the content of information, namely on alternative items and the risk of 57 informed consent (39.3%). The conclusion of the analysis of the completeness of filling the informed consent sheet of lung surgery patients at Pasar Minggu Hospital is still incomplete. Factors that cause incomplete informed consent among others are the understanding of doctors who are still lacking about the importance of informed consent, limited doctor time, busyness of doctors, dependence of doctors to nurses, lack of attention of doctors to fill informed consent, sop hospitals that are still not implemented to the maximum, and the absence of punishment and reward in hospitals.